Power allocation for an energy harvesting transmitter with hybrid energy sources - Ahmed, Imtiaz; Ikhlef, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
In this work, we consider a point - to - point communication link where the transmitter has a hybrid supply of energy. Specifically, the hybrid energy is supplied by a constant energy source and an energy harvester, which harvests energy from its surrounding environment and stores it in a battery which suffers from energy leakage. Our goal is to minimize the power consumed by the constant energy source for transmission of a given amount of data in a given number of time intervals. Two scenarios are considered for packet arrival. In the first scenario, we assume that all data packets have arrived before transmission begins, whereas in the second scenario, we assume that data packets are arriving during the course of data transmission. For both scenarios, we propose an optimal offline transmit power allocation scheme which provides insight into how to efficiently consume the energy supplied by the constant energy source and the energy harvester. For offline power allocation, we assume that causal and non - causal information regarding the channel and the amount of harvested energy is available a priori. For optimal online power allocation, we adopt a stochastic dynamic programming (DP) approach for both considered scenarios. For online power allocation, only causal information regarding the channel and the amount of harvested energy is assumed available. Due to the inherent high complexity of DP, we propose suboptimal online algorithms which are appealing because of their low complexity. Simulation results reveal that the offline scheme performs best among all considered schemes and the suboptimal online scheme provides a good performance - complexity tradeoff. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: convex optimization; dynamic programming; Energy harvesting; hybrid energy supply; power allocation